Enhancing teacher innovative practices through principal learning-centred leadership and teacher knowledge sharing - Arslan, Kürşat; Savas, Gokhan; Kılınç, Ali Çağatay (Wiley, 2026)
This study developed and tested a mediated-effects model to examine how learning-centred leadership influences teacher innovative practices through teacher knowledge sharing within T & uuml;rkiye's centralised education system. Using survey data from 405 primary and secondary school teachers across T & uuml;rkiye, we performed structural equation modelling to analyse the empirical links among study variables. The findings indicated that learning-centred leadership has a significant direct impact on teacher innovative practices and an indirect effect through teacher knowledge sharing. Grounded in social exchange theory, our study suggested that principals who execute learning-centred leadership practices foster teacher knowledge sharing, which, in turn, enhances teachers' implementation of innovative practices. We provided implications for policymakers and practitioners in T & uuml;rkiye and similar educational contexts who aim to improve teacher innovative practices.
Keywords: learning-centred leadership; mediated-effects model; social exchange theory; teacher innovative practices; teacher knowledge sharing